High-Sensitivity Low-Temperature Poly-Silicon Lateral Photodetector with Ultrathin Absorption Layer via Body-Extension-Contact Structure - Wei, Yin-Chang; Lee, I-Che; Cheng, Huang-Chung (My University, 2016)
A high-sensitivity lateral photodetector (PD) with an ultrathin absorption layer was fabricated by a low-temperature poly-silicon (LTPS) process via body-extension-contact (BEC) structure. The sensitivity of the LTPS PD with the BEC structure achieved a superior photo/dark current ratio of 105 compared to the ratio of 10(0.5) for the normal PD. Further, for the first time, the effect of photosensitivity and geometry on the ideality factor (n) was investigated in this study. The developed high-performance PD is suitable for application in image scanners, ambient light sensors, or devices embedded in larger area electronics.
Keywords: Low-Temperature Poly-Silicon (LTPS); Photodetector (PD); Body-Extension-Contact (BEC) Structure